(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis Income of California Papaya Farm (Carica papaya L.) in Sibang Gede Village, Abiansemal District, Badung Regency. California papaya is a horticultural crop that is widely produced in Indonesia. This research aims to calculate the income of California papaya farmers in Sibang Gede Village. The research was carried out during one planting period, from February 2022 to September 2023. The sampling technique used saturated samples with non-probability sampling. The samples taken were six people. The data analysis used is analysis of farming income by calculating farmer income and farming costs. The parameters used are production quantity, selling price, quantity and price of fertilizer, seeds, tools, labor, pesticides. The research results show that the average area cultivated for California papaya in Sibang Gede Village is 1.01 Ha with an average production in 2023 of 13,750 kg and an average selling price of 5,000 per kg, income received by farmers of IDR 56,668,388 per planting period. and per cultivated area while IDR 56,107,314 per planting period and per hectare. R/C value of 5,7 indicates that farming is worth pursuing. This shows that farmers can maintain California papaya farming because expenses can be covered by income. Farmers’ income can also be increased if problems in farming can be resolved properly. It is recommended that farmers overcome existing problems on the land so that income can increase.